2018
DOI: 10.1111/jerd.12405
|View full text |Cite
|
Sign up to set email alerts
|

Perception of facial, dental, and smile esthetics by dental students

Abstract: Appropriate perception of facial, dental and smile esthetics by dental students is of paramount importance for providing adequate dental services and for improving and polishing their professionalism.© 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 27 publications
7
26
1
6
Order By: Relevance
“…These results are comparable to those of other publications [29,39]. A coincident midline is the most prevalent presentation in nature and must be respected in prosthetic dental treatment in order to ensure an aesthetic outcome [33,40]. Silva et al [7] found the threshold for perceiving a deviation of the maxillary interincisal midline with respect to the facial midline to be 2 mm, in coincidence with the observations of other authors [16,18].…”
Section: Discussionsupporting
confidence: 85%
“…These results are comparable to those of other publications [29,39]. A coincident midline is the most prevalent presentation in nature and must be respected in prosthetic dental treatment in order to ensure an aesthetic outcome [33,40]. Silva et al [7] found the threshold for perceiving a deviation of the maxillary interincisal midline with respect to the facial midline to be 2 mm, in coincidence with the observations of other authors [16,18].…”
Section: Discussionsupporting
confidence: 85%
“…In the study of Armalaite et al [12], shifted maxillary midline was classified by both male and female (4 th -and 5 th -year) dental students as unacceptable. Alhammadi and co-workers report that the dental students in their study noticed as small a shift as 1 mm [23]. It seems, thus, that the position of the maxillary midline is a sensitive esthetic issue, so it came as no surprise that in our study it was one of the parameters significantly associated with the stage of studies.…”
Section: Discussionsupporting
confidence: 44%
“…They drew the conclusion that women were "more critical" regarding these features. Finally, Alhammadi and colleagues [23] studied 408 Saudi Arabian dental students, and came to the conclusion that "male dental students have a better perception of facial and dental esthetics." It is not clear if the remarkable difference between the results of these studies is due to the different geographical locations, the difference between the studied features or something else.…”
Section: Discussionmentioning
confidence: 99%
“…El instrumento de evaluación utilizado fue la escala VAS la cual brinda un puntaje confiable (30) y es un método de uso común para nociones subjetivas como el dolor, atractivo y ansiedad en investigaciones de ciencias de la salud; aunque existe la tendencia de algunos evaluadores de no utilizar toda la escala debido a que tienen temor de dar una calificación alta a una imagen, en caso de que la siguiente les parezca más estética (31), para compensar esto y limitar el posible cansancio visual se decidió evaluar sólo tres posiciones en cada una de las variables estudiadas, a diferencia de otros estudios en dónde evaluaron mayor cantidad (1)(2)(3)(4)(5)(8)(9)(10).…”
Section: Discussionunclassified
“…En los últimos años la búsqueda de una adecuada estética facial y dental, ha tomado mayor importancia para los pacientes, siendo la sonrisa un elemento primordial en ello. Actualmente es frecuente someterse a diferentes tratamientos estéticos y cosméticos en las diversas especialidades médicas y odontológicas, sin embargo, no existe un consenso entre ortodoncistas, dentistas, estudiantes de odontología, pacientes y personas comunes en lo que se considera una sonrisa estética (1)(2)(3)(4)(5), esto se debe posiblemente a la naturaleza subjetiva de la sonrisa y a que durante muchos años solo se tomó en cuenta la opinión de algunos autores y no de una literatura basada en evidencias (6,7). Es importante mencionar que en la planificación del tratamiento ortodóntico y en la finalización, el objetivo principal ha sido lograr una oclusión estable con una adecuada función y esto no necesariamente coincide con una sonrisa estética en el sector anterior (8)(9)(10).…”
Section: Introductionunclassified